The Use of Wordwall in Teaching English Vocabulary to Seventh-Grade Students at Islamic Junior High School - Habibatul Husna Ismail (GENRE JOURNAL : Journal of Applied Linguistics of FBS Unimed, 2025)
This study explores the use of Wordwall in teaching English vocabulary to seventh-grade students at an Islamic Junior High School and investigates the teacher's perception of this digital tool. It employs a descriptive qualitative design using the TPACK (Technological Pedagogical Content Knowledge) framework by Mishra and Koehler (2006) and the Technology Acceptance Model (TAM) by Davis (1989). Data were collected through classroom observation, interviews, and documentation. Observation focused on TPACK indicators, while interviews were based on TAM dimensions: Perceived Usefulness (PU) and Perceived Ease of Use (PEOU). Findings reveal that the teacher could independently operate Wordwall and adapt it to student characteristics using contextual and kinesthetic strategies. The teacher perceived Wordwall as easy to use and effective in enhancing student motivation and vocabulary comprehension. Despite minor technical challenges, the teacher managed them with appropriate strategies.